2015
DOI: 10.1097/sla.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Occult Penetrating Cardiac Injuries

Abstract: The sensitivity of US to detect hemopericardium in stable patients was only 86.7%. The 2 main factors that limit the screening are the presence of a hemothorax and air in the pericardial sac. A new regimen for screening of occult injuries to make allowance for this is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 36 publications
2
48
0
3
Order By: Relevance
“…Although US is advocated as an accurate and sensitive tool to detect a hemopericardium [28][29][30][31], the presence of hemothorax and/or pneumopericardium confounds the interpretation of US and may lead to a high number of false-negative investigations. In case of equivocal US results or the presence of a hemothorax, CT is the adjunctive of choice to screen for occult penetrating cardiac injuries or repeat US at 24 h once the hemothorax has cleared [32]. In only 10.4% of all patients presenting with diagnosed PTI, there was a primary indication for surgical treatment: EDT (2.4%), UTS (3.2%), and planned SXW (4.8%).…”
Section: Discussionmentioning
confidence: 96%
“…Although US is advocated as an accurate and sensitive tool to detect a hemopericardium [28][29][30][31], the presence of hemothorax and/or pneumopericardium confounds the interpretation of US and may lead to a high number of false-negative investigations. In case of equivocal US results or the presence of a hemothorax, CT is the adjunctive of choice to screen for occult penetrating cardiac injuries or repeat US at 24 h once the hemothorax has cleared [32]. In only 10.4% of all patients presenting with diagnosed PTI, there was a primary indication for surgical treatment: EDT (2.4%), UTS (3.2%), and planned SXW (4.8%).…”
Section: Discussionmentioning
confidence: 96%
“…We suggest that stable patients with penetrating thoracic injury should undergo thoracic CT. FAST/ echocardiography is operator-dependent and might miss a cardiac injury due to a pneumothorax or a lack of tamponade, when the pericardium has been decompressed by blood entering the pleural cavity [ 24 , 25 ]. Pericardial fluid or air on CT might indicate cardiac injury and the question of surgery vs conservative treatment arises.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in the performance and interpretation of cardiac ultrasound in penetrating trauma appear to be in patients with a co-existent hemothorax [26,28] air in the pericardial sac [29], and also lacerations of the pericardial sac [30]. This may be because the fluid accumulates into the thoracic cavity rather than the pericardium, or that it the hemothorax obscures the pericardium and makes differentiation of anatomical planes difficult.…”
Section: Discussionmentioning
confidence: 97%
“…The authors found that, if there is presence or suggestion of either hemothorax or pneumopericardium, then further diagnostic testing is required [29]. Similarly, a 2009 study, found that the numbers of false negatives were increased with concurrent lacerations of the pericardial sac secondary to sequestration of the blood into the thoracic cavity therefore preventing accumulation of a hemopericardium [30].…”
Section: Ultrasound For Penetrating Cardiac Injurymentioning
confidence: 99%